Fish species assemblages and diversity in water body infested by alien species - Siti Nur Atikah Mohammad; Iqbal Harith Abd Razak; Akmal Amalina Mohd Fauzi; Nurhidayah Azlan-Hisyam; Martin, Melissa B.; Nelson, Bryan R.; Muhammad Hafiz Borkhanuddin; Mohamad Aqmal-Naser; Amirrudin Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Human is one of the mediators for non-native species invasion, especially in the aquatic ecosystem. Aquaculture and sport fishing activities are the main reasons for non-native fish introduction, especially in man-made habitats. In the present study, we determined the fish community between the invaded as opposed to pristine ecosystems in north Terengganu, Malaysia. The primary data was collected using hook and line, hand-held push net, cast net and gills net while secondary data were also utilised from published and unpublished data. The fish general information including functional traits and prey-predator relationship were obtained from literature and reliable online resources. The data were used to construct hypothetical diagrams and analyzed using taxonomic distinctness index. The fish community between the two habitats differ significantly in which the non-native fish invaded habitat has much lesser fish species richness than that of the pristine habitat. Taxonomic diversity between the two habitats also was markedly different. The non-native Cichla ocellaris added predation pressure to fish community in the lacustrine habitat as the apex predator and were proven to feed on the native fish fauna in the lake. We discuss the community structure in both habitats and explore the further impact of invasion by this invasive alien species on the native fish species. We conclude that the presence of Cichla ocellaris amplify pressure to native fish community in the man-made lake.